Request for harmonisation of regulation related to closer regulation of conditions for conducting professional jobs in institutions for social protection and licensing with the current law on social protection - Redakcija, Sociološki pregled (Sociološki pregled, 2018)
Request for harmonisation of regulation related to closer regulation of conditions for conducting professional jobs in institutions for social protection and licensing with the current law on social protection